Child abuse myths are pedophilic myths: cognitive distortions are stronger in individuals convicted of sexual offenses diagnosed with pedophilia compared to those without such diagnosis - Eberhaut, Sabrina (Deviant behavior, 2023)
Based on the theory of cognitive dissonance and the understanding of cognitive distortions as defense mechanisms, we argued that individuals convicted of sexual offenses diagnosed with exclusive pedophilia (epICSOC) report more child offense related cognitive distortions compared to individuals convicted of sexual offenses without such diagnosis (oICSOC). In the present study, we aimed to empirically validate these clinical observations and previous results by relating cognitive distortions to four measures of pedophilic preference, namely, a clinical diagnosis of pedophilia, viewing time captured and self-reported pedophilic preference (EISIP; as well as the SSPI-2). Results revealed that cognitive distortions in general and minimizing sexually offending behavior toward children or attributing sexual interest to children in particular, significantly correlated with all four measures of pedosexual preference. Regression analyses, furthermore, indicated that attributing sexual interest to children was the best predictor for a pedosexual preference. Results thus show that cognitive distortions typically associated with child molesting in general are, in fact, more common in individuals convicted of sexual offenses diagnosed with exclusive pedophilia than in those without such diagnosis.